Recent Progress in Lithium Lanthanum Titanate Electrolyte towards All Solid-State Lithium Ion Secondary Battery. Issue 4 (4th July 2019) - Sun, Yuandong; Guan, Peiyuan; Liu, Yunjian; Xu, Haolan; Li, Sean; Chu, Dewei
Abstract: Lithium lanthanum titanate (LLTO) is one of the most promising solid electrolytes for next generation batteries owing to its high ionic conductivity of ∼1 × 10 − 3 S/cm at room temperature. To comprehensively understand the microstructure and ion diffusion mechanism of LLTO, recent research in diffraction and spectroscopy techniques as well as computational study have been reviewed in this paper. The extremely low ionic conductivity at grain boundary as well as the increased electronic conductivity related to the direct contact with metallic lithium has impeded the practical application of LLTO for the solid-state batteries. Various studies including substitution, the introduction of grain boundary layer modifier, high temperature sintering, and synthesis of amorphous LLTO have been applied to solve these major challenges and their effectiveness are discussed in this review. Moreover, different types of synthesis methodologies of LLTO thin films are reviewed and compared in detail. In the end, the recent reports of solid-state battery system are reviewed and discussed.